Using Institutional Resources and Agency to Support Graduate Students’ Success at a Hispanic Serving Institution - Natalie A. Tran; Gaetane Jean-Marie; Katherine Powers; Sean Bell; Kimberly Sanders (Education Sciences, 2016)
There is a growing body of evidence that links increased social capital to minority student success in college. This paper seeks to expand specifically on the graduate experience of underrepresented minorities (URM) at a Hispanic Serving Institution (HSI) using the social capital framework. In a cross-sectional survey, 198 graduate students retrospectively considered the role of institutional resources and agents in their success towards graduation. Data revealed that motivational factors such as a sense of personal achievement, family support, peer support, career promotion, supportive faculty, program satisfaction, and faculty mentor played critical roles in the success of graduate students at HSI. Specifically, Latino students are more likely to report that faculty mentors played a significant role in their success compared to their non-Latino peers χ2(1, N = 195) = 5.33, p = 0.02. Latinos/as were also more likely to use writing support services than their non-Latino/a peers χ2(2, N = 190) = 7.59, p = 0.02. By identifying and increasing access to institutional resources and agents, underrepresented minorities in post-baccalaureate programs may encounter less barriers to graduate degree success.